Two-dimensional ferroelasticity in van der Waals β’-In2Se3 - Chao Xu (Nature Portfolio, 2021)
Ferroelasticity is predicted theoretically in 2D materials, but it lacks experimental validation. Here, the authors find 2D ferroelasticity in both exfoliated and CVD-grown β’-In2Se3 down to few-layer thickness by atomic-resolution electron microscopy, in situ X-ray diffraction, and polarized-light microscopy.